Sustainable livelihood model for ethnic minority regions – case study in Quang Ninh province - Ngoc, Ho Sy; Tung, Trinh Van; Doan, Ta Thi; Long, Pham Hoang; Hau, Ha Thi (Edelweiss Applied Science and Technology, 2025)
When addressing the issue of livelihood, people often refer to the ways ethnic groups or communities sustain their living amidst the impacts of various environmental and socio-economic factors. These factors include: (i) loss of cultivated land due to rising sea levels, landslides, and increased droughts; (ii) reduction of arable land caused by salinity intrusion, erosion, and leaching; and (iii) increased crop failures, decreased productivity of crops and livestock resulting from rising temperatures, unusual weather patterns, extreme climate events, and epidemics. These challenges significantly affect the lives and survival of people under current conditions. Particularly for ethnic minorities in the Northeast region, they tend to be economically disadvantaged, with limited access to modern production methods, and are at higher risk of being adversely affected during the overall development process of their communities. According to current zoning conditions, the Northeast region includes provinces such as Phu Tho (which merges the three provinces of Phu Tho, Vinh Phuc, and Hoa Binh), Tuyen Quang (which merges Ha Giang with Tuyen Quang), Cao Bang, Thai Nguyen (which merges Bac Kan with Thai Nguyen), Lang Son, Bac Giang (the old Bac Giang, now merging with Bac Ninh), and Quang Ninh. As per the spirit of Resolution No. 202/2025/QH15 passed by the National Assembly on June 12, 2025, these areas are significantly affected by the aforementioned factors. A case study conducted in Quang Ninh province highlights several limitations in addressing livelihood issues: (1) livelihood conversion heavily depends on the mining industry, making occupational shifts difficult; (2) uneven quality of human resources acts as a major barrier; (3) unsustainable tourism development leads to various negative consequences; (4) income disparities between regions pose significant challenges in solving livelihood problems; and (5) policy mechanisms are not yet fully synchronized, complicating integration with poverty reduction programs and the promotion of regional advantages.